Quality analysis of Worldview-4 DSMs generated by least squares matching and semiglobal matching - Sefercik, Umut G.; Alkan, Mehmet; Jacobsen, Karsten; Atalay, Can; Buyuksalih, Gurcan (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2021)
For the estimation of a dense disparity map from a rectified space-borne stereo image pair and generation of the most qualified digital surface model (DSM), new image matching algorithms are being developed. Our study has two main goals of the DSM quality validation of Worldview-4 (WV-4), which offers the highest ground sampling distance (GSD) (30 cm) of civilian optical space-borne missions together with Worldview-3 (WV-3), and performance comparison of semiglobal matching (SGM) and least squares matching (LSM), two of the most preferred image matching algorithms for space-borne data. In the Istanbul study area with a rough topographic structure, 1 m gridded DSMs were derived from geometrically corrected WV-4 stereo image pairs. The qualities were estimated by well-rounded visual and statistical approaches based on standard deviation and normalized median absolute deviation. In modelto-model comparisons, a very high-resolution airborne laser scanning (ALS) DSM was utilized as the reference model. The results demonstrated that the WV-4 DSM derived by SGM has the standard deviation of +/- 0.51 m (1.7 GSD) in height in open areas, whereas the LSM DSM has +/- 1.46 m. In addition, the visual quality of SGM is much better than LSM through building description potential. (C) 2021 Society of Photo-Optical Instrumentation Engineers (SPIE)
Keywords: Worldview-4; least squares matching; semiglobal matching; digital surface model; quality; RATIONAL FUNCTIONS; STEREO-IMAGES; MODELS; EXTRACTION; ORIENTATION; Environmental Sciences & Ecology; Remote Sensing; Imaging Science & Photographic Technology